Altered Passive Eruption and Familial Trait: A Preliminary Investigation - Roberto Rossi; Giorgio Brunelli; Vincenzo Piras; Andrea Pilloni (Hindawi Limited, 2014)
Altered passive eruption is described as a condition in which the relationship between teeth, alveolar bone, and the soft tissues creates an excessive gingival display and, in turn, in some circumstances, it may reveal a clinical aspect also known as the "gummy smile." The surgical management of such cases is well understood and has been widely described, with mucogingival and osseous resective procedures being predictable surgical means leading to more balanced aesthetics and proper display of the teeth anatomy. The possible familial trait in case of passive eruption and therefore the possibility of recurrence of the same condition in families of siblings or parents of affected patients have been investigated in this study. 20 patients have been selected and treated in both a private practice and university settings and their immediate family trees were evaluated in order to understand the incidence of the condition. 65% of the treated patients had one or more family members with the same condition leading to seeking further investigation on the possible genetic correlation.